The Effect of Herbicides (2,4 Dichlorophenoxic Acid) on the Early Stages of Development of Winter and Spring Wheat Varieties - Haydarov Hislat Kudratovich, Ismatova Zilaykho Asadovna, Pardaboyev Sherzod Tohir ugli; Boltayev Ozod Toshtemirovich (International Journal of Advanced Science and Technology, 2020)
This article describes in detail herbicide resistance of spring and winter wheat, as well as the negative and positive effect of herbicides on seedlings. The study was conducted at various concentrations of herbicides, and for each concentration, individual morphological characteristics of plant seedlings were analyzed. The experiments were carried out in laboratory conditions in the roll method and Petri dishes. The experiments were carried out in laboratory conditions in the roll method and Petri dishes. 10 morphophilic traits (total length, total weight, weight of the upper part, length of the upper part, width of the first leaf of the plant, width of the first leaf (mm), number of roots, length of the root, weight of the root, upper part weight and root weight ratio) were analyzed and tabulated in the roll method, 6 in wheat and in experiments in Petri dishes (total length, total weight, upper part length, hypocatyl length, number of roots, root length). Statistics of changes in the concentration of herbicides according to the morphological characteristics of the seedlings was studied and presented in tables.